MODEL PENGELOLAAN LINGKUNGAN PADA INDUSTRI KECIL MENENGAH (IKM) DI KOTA SEMARANG - Budhi Cahyono (Jurnal Ekonomi dan Bisnis, 2011)
The objective of this study is to analyze the impact of environmental initiative, employee involvement, and supplier integration on the environmental performance and corporate performance Semarang municipality. This study uses environmental initiative, employeeinvolvement, and supplier integation as an exogenous variable, and such intervening variables as environmental performance, and dependen variable is corporate performance. The first step of the study is to investigate the influence of environmental initiative, employee involvement, and supplier integtarion on environmental performance. The second step is to investigate the influence of environmental performance on corporate performance. The third step is to investigate new model of environment management based on the trimming theory. The population of this study consists of 85 corporetes where operations on industrial centre in Semarang municipality. All of the variables are measured with four indicators for every indicators. The analysis data using path analysis that solved by multiple regression. The result of the study shows that, first: the independent variables environmental initiative and employee involvement have significant influence on environmental performance. Second, supplier integration has direct effect on corpporate performance. Third, environmental management has a significant influence on corporate performance. At last, the result of trimmed model show that environmental performance as a mediating variables from correlations amoong environment initiative, employee involvement on corporate performance.Keywords:Environmenalt Initiative, Employee Involvement, Supplier Integration, Environmental Performance, and Corporate Performance.